Parent’s Knowledge and Attitude as Key Determinants of Completeness Childhood Immunization in Central Java, Indonesia - Sriatmi, Ayun; Martini, Martini; Jati, Sutopo Patria; Budiyono, Budiyono; Handayani, Novia; Kusumawati, Aditya; Armunanto, Armunanto (Jurnal Kesehatan Masyarakat, 2024)
Incomplete basic immunization in children aged 11-23 months has potential to increase contracting dangerous diseases risk due to suboptimal immunity. Parents play an important role in ensuring the success of children immunization. This study purpose was to analyze the completeness of CBI based on parents' knowledge, attitude, perception, and satisfaction in immunizing their children. It’s a quantitative analytic study with cross sectional approach. The population were all children with sample of 685 children taken by purposive sampling technique from 31 districts in Central Java province. Data were collected through interviews and analyzed univariate with frequency distribution, bivariate with Chi-Square test, and multivariate with multiple logistic regression. A total of 38.7% children were not fully immunized, especially in booster immunization (73.4%), IPV (25.7%) and MR (15.9%). Partially, it was proven that parent’s knowledge, attitude, perception, and satisfaction were related to completeness of basic immunization. Simultaneously knowledge and attitude together affect the completeness of basic immunization in children with an overall effect of 42%. Parents' knowledge and attitudes are key factors for completeness of basic childhood immunization. Need to improving literacy and strengthening positive attitudes through structured IEC using personal approach, as well as involving key figures in the community in their support for immunization program. Utilizing communication technology and social media is an alternative that should be considered.